Pressure-volume Relationship for Platinum and Aluminium - Saud Khan, Mahendra Mehra, Rajendra Kumar; Salil Dubey, Tanveer Ahmad Wani*, Pankaja Singh, A. (Journal of Experimental Sciences, 2011)
Platinum and Aluminium are widely used as a pressure calibration standard. The present proposal which intends to compare the efficiency of the four equations under close examination reports the V/VO versus P values derived from the new modified forms of Murnaghan equation NMME1, NMME2, Birch equation (BE) and Freund-Ingalls (FIE) obtained for the best agreement with the experimental data of Mc Queen et.al.